Trainee involvement increases precut rates and delays access to the common bile duct without an increase in procedure-related adverse events: a brave new world of ERCP training? - Voiosu Theodor; Voiosu Andrei; Benguş Andreea; Rimbaş Mihai; Mateescu Bogdan (Sciendo, 2018)
Background and aims. Selective cannulation of the desired duct is a key element in ERCP procedures and an important step in the training of fellows. However, there is limited data about technical success and patient safety for ERCPs conducted in a training setting.We aimed to evaluate the impact of trainee involvement on the cannulation technique and procedure related outcomes at ERCP.